Enhanced thermal performance in a square-duct heat exchanger with inclined square-rings - Chitakorn Khanoknaiyakarn; Pitak Promthaisong; Panuwat Hoonpong; Pongjet Promvonge; Sompol Skullong (IOP Conference Series Materials Science and Engineering, 2021)
Abstract An experimental work has been conducted to explore thermal and turbulent flow friction characteristics in a uniform heat-fluxed square-duct contained with inclined square-rings (SR). Experiments were performed for different geometric parameters of the SR elements, focused on their detailed effects on the optimal thermal performance. Influences of five different ring-to-duct height or blockage ratios (BR=b/H= 0.1, 0.15, 0.2, 0.25 and 0.3) on friction factor ( f ), Nusselt number (Nu), and thermal enhancement factor (TEF) in the square duct are investigated for Reynolds number (Re) from 4210 to 25,800. The inclination angle (a) and the ratio of axial pitch length of rings to the height of duct (called pitch ratio, PR=P/H) were kept constant at 60° and 3.0, respectively. The experimental result has shown that the SR insert gives greater heat transfer and friction loss than the plain duct acting alone. Increasing the blockage ratio (BR) results in the drastic enhancement in Nu and f values. The inserted duct with BR = 0.25 has the maximum TEF around 1.57. Comparing thermal performance at identical operating conditions, the SR insert at BR = 0.15 gives around 1.1 %, 2.3 %, 3.2 and 4.5 % higher than the one at BR = 0.2, 0.25, 0.3 and 0.1, respectively.
Keywords: Heat Transfer Mechanisms; Heat Transfer and Optimization; Fluid Dynamics and Turbulent Flows